Feco-prevalence of Helicobacter Pylori among symptomatic patients in Al-Marj city - Ali Mohammed Salih, Salah; Ali S. Abbas, Ghada; Mohammed, Monier; MK Abdeldaim, Guma (Libyan Journal of Public Health Practices, 2025)
Helicobacter pylori is a bacterium that causes infections in a significant portion of the global population. This study aimed to determine the prevalence of H. pylori infection among dyspeptic patients and to investigate its association with age and sex in Al Marj City, Libya. A cross-sectional descriptive study was conducted at Tabebouk Laboratory from January 1, 2023, to December 31, 2024, involving 495 participants. Stool samples were analysed using a fluorescence immunoassay-based technique to detect H. pylori antigens. The overall prevalence of H. pylori infection was 50.3%, with males showing a higher infection rate (54.22%) than females (45.78%). The highest prevalence was observed in young adults aged 20-45 years (49.40%), followed by middle-aged and elderly individuals (≥46 years; 36.95%). Children and teenagers had significantly lower infection rates (6.83% each). No significant sex differences were found among children and teenagers. In conclusion, H. pylori infection rates were higher in males and most prevalent among young adults aged 20–45 years. These findings highlight the need for targeted public health strategies, especially in adult populations, to improve early detection and management of H. pylori-related gastrointestinal conditions.